Механізми формування пропозиції та попиту на послуги з енергоефективності - Люльчак, З. С.; Lyulchak, Z. (Видавництво Львівської політехніки, 2019)
Актуалізовано концепцію енергоефективності у забезпеченні досягнення цілей сталого розвитку. Ідентифіковано макрочинники та бар’єри впровадження заходів із енергоефективності. Обґрунтовано засади та тренди формування бізнес-сегменту на ринку енергії – ринку послуг з енергоефективності. Здійснено позиціонування послуги з енергоефективності за трьома вимірами: матеріальний / нематеріальний компоненти, індивідуальність / стандартність послуги та безпосередність / опосередкованість контакту з клієнтами. Виокремлено суб’єктів ринку постачальників послуг із енергоефективності (ППЕ), щодо яких здійснено оцінювання конкурентного середовища.

The importance of improving energy efficiency in production, transmission, distribution and trade, as well as the use of energy for the implementation of sustainable development policies in the country, has been established. The concept of “energy efficiency” based on the analysis of literary sources is specified. The factors of influence on the implementation of energy efficiency and its barriers were identified. The energy policy instruments for energy efficiency in the processes of energy production and use were highlighted: energy efficiency certificates, energy efficiency audits of buildings and energy audits of enterprises. The mechanisms of demand and supply formation at the energy efficiency field were identified. These include mechanisms for pricing, regulation and control, development of financial measures and tax incentives, market development, technological development, commercial development and the creation of energy efficiency and financial recovery potential. Their impact on energy demand and supply generation has been identified. It is established that the mechanism of regulation of energy efficiency is aimed at achieving parity between the demand for energy efficiency services and the supply of these services. Ukraine bases its energy efficiency policy on the basis of the EU energy and environmental strategies. Improving energy efficiency has a positive impact on generating benefits in many areas of the Ukrainian economy. These include: an increase in the value of assets, energy saving, energy security of the country, revenue growth, restructuring of the country’s budget structure, cleaning the environment, increasing the efficiency of processes, reducing the cost of energy supply, lowering energy prices, developing innovative production, and increasing competitiveness. Nowadays, in the Ukrainian energy market we can distinguish a segment – the providers of energy efficiency services – which in turn causes the operating with terms such as “demand of energy efficiency services” and “supply of energy efficiency services”. Consulting services, the development of technical assistance programs and the preparation of an international feasibility study are in greatest demand. Incomplete demand was found in the area of bringing energy efficiency projects to the implementation stage. The definition of energy efficiency service was clarified according to the following parameters: tangible – intangible components; direct contact with the client – indirect contact with the client; standard service – unique service. It has been established that the service on electrical efficiency is mainly intangible, standardized, service providers work with clients without intermediaries. The analysis of the market segment of energy efficiency service providers according to the model of M. Porter has been carried out. Scoring allowed the following conclusions to be drawn: a low level of threat from a substitute service; average level of intra-industry competition; high level of threat of new participants entering the market; medium level of threat of a customer replacing a service provider; the average level of influence of suppliers is manifested in the case of activities in the field of renewable energy. It has been established that the market segment of energy efficiency service providers is at the saturation stage.
Mechanisms of demand and supply formation for the services of energy efficiency
Keywords: послуги з енергоефективності; механізми формування попиту і пропозиції; постачальники послуг з енергоефективності; позиціонування послуги з енергоефективності; energy efficiency service; mechanisms of demand and supply; providers of energy efficiency service; the positioning of energy efficiency service; 658.7; 338.246